THE ROLE OF UNICEF IN FULFILLING CHILDREN'S RIGHT TO EDUCATION IN INDONESIA - Putri, Marini Syifa Sari; Yuniarti, Sri; Soelistijono, Pra Adi (Universitas Islam Indonesia, 2025)
Education is a basic right of every child recognized in various international and national legal instruments, including the Convention on the Rights of the Child (KHA) and the 1945 Constitution of the Republic of Indonesia. Although the Indonesian government has adopted various policies to guarantee children's right to education, disparities in access to education remain a major challenge, especially for children from economically disadvantaged backgrounds and remote areas. The United Nations Children's Fund (UNICEF) plays an important role in supporting the fulfillment of children's right to education in Indonesia through various programs and cooperation with the government. This study aims to analyze the role of UNICEF in efforts to fulfill children's right to education in Indonesia, especially in the context of the role of international organizations as instruments according to Clive Archer's concept. The research method used is descriptive qualitative with a literature study approach and secondary data analysis. The results show that UNICEF plays a significant role in overcoming barriers to children's education through the implementation of innovative programs and strengthening cross-sector partnerships with various stakeholders. This research emphasizes the importance of the role of international organizations, such as UNICEF, in supporting the fulfilment of the right to education and promoting the nation's progress in a sustainable manner.